Optimizing the Performance of Archivist Human Resources through AppSheet at the Ponorogo Regency Library and Archives Office - Silvi Sitaviana; Sri Indrahti (International Journal of Economics, Business and Accounting Research (IJEBAR), 2022)
The purposes of this study is optimizing the performance of archivist human resources though AppSheet at Ponorogo Regency Library and Archives Office. The research method used is a mixed method (qualitative and quantitative). Data collection techniques include library research, experiments, and interviews. Data analysis techniques using qualitative and quantitative. The results show that AppSheet is effective for optimizing the performance of archivist human resources because of the eight keywords, all of them are 100% accurate and the retrieval time is 6-10 seconds. Keywords: Effectiveness, AppSheet, Photo Inactive Archives, Library and Archives Service of Ponorogo Regency